Philosophical suicide between Socrates and Foucault - محمد, سعاد (Latakia University Journal - Arts and Humanities Sciences Series, 2022)
The philosophical position is considered a dividing line between the idea and its practical application, because the ideas adopted by the philosopher lose their truth if they do not receive an appropriate defense for them. In this research, we try to approach two philosophical positions taken in defense of a message containing ideas adopted by its owners, so we see Socrates, who chose death by drinking poison in compliance with the laws that he revolted against and rejected, And (Gordano Bruno), who was tortured in the most horrific forms of torture in defense of his sciences, research and ideas until his last breath.